Knowledge Representation in Map Collections for Information Retrieval Systems - Babik, Wieslaw (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
In this article, I will deal with the issue of the knowledge representation about maps kept in libraries or available through Internet from the viewpoint of information retrieval. Representation of knowledge belongs to those fields, which have undergone dynamic change in recent decades. The interest it not only raises among specialists, but also among librarians and information scientists indicates the viability of this field of study. Many scholars conduct research in the respective areas. Articles on the subject related to the documentation are also published. The knowledge of the contents of a map collection is represented in the information retrieval system by metainformation kept in databases, which also perform regular retrieval process. Indeed, we are talking about the problems of access to the contents of map collections through respective information retrieval systems requiring such a system of map description and formal and subject cataloguing which would allow for searching maps relevant to the needs of their users. Using documentation terminology, first of all we mean the issue of information retrieval languages designed for such collections and primarily the method of representing knowledge for the needs of such materials classification which so far may be one of the basic tools of map collection organisation.